1997
DOI: 10.1046/j.1365-3024.1997.d01-214.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro infection with Theileria parva is associated with IL10 expression in all bovine lymphocyte lineages

Abstract: The protozoan parasite Theileria parva infects and transforms bovine lymphocytes, giving rise to a fatal lymphoproliferative condition known as East Coast fever. Although immune cattle mount strong cytolytic T lymphocyte responses to the parasite, naive animals appear unable to respond and develop severe immunopathological lesions. We have investigated the patterns of cytokine mRNA expressed by 19 bulk and cloned parasite-infected lymphoblast cell lines using a multiplex PCR system. Considerable variation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…The expression of IL-10 mRNA was shown to be up-regulated as protozoan DNA load was increased. As mentioned above, IL-10 has been reported to be expressed in all T. parva-transformed cell lines examined [19]. The role of IL-10 in the pathogenesis of the disease is unclear, but IL-10 may be induced as a part of a homeostatic network that protects tissues from collateral damage by excessive inflammation [20].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The expression of IL-10 mRNA was shown to be up-regulated as protozoan DNA load was increased. As mentioned above, IL-10 has been reported to be expressed in all T. parva-transformed cell lines examined [19]. The role of IL-10 in the pathogenesis of the disease is unclear, but IL-10 may be induced as a part of a homeostatic network that protects tissues from collateral damage by excessive inflammation [20].…”
Section: Discussionmentioning
confidence: 93%
“…In the previous studies, a T cell clone infected with T. parva appeared to express higher cytokine mRNAs (IL-6 and TNF-α) than an infected B cell clone [19], and T cells infected with T. parva stimulated autologous cells more efficiently than infected B cells [9]. In addition, the inoculation of cattle with T. parva-infected B cells has been shown to cause a mild to modest disease [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is likely that losing all the three transcriptional activities, combined with reduced c-Myc stability, probably explains the very rapid drop in c-Myc levels observed upon parasite death in Figure 1b. Finally, the ablation of STAT3 phosphorylation by AG490 treatment that precedes reduction in c-Myc (Figure 1, panel c) might be due to continued JAK1 signalling to c-myc perhaps via STAT5, as this combination can be activated by a number of cytokines, such as IL-10 known to be secreted by Theileria-transformed lymphocytes (Mckeever et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, parasitedependent regulation of Lyn, Fyn, and Lck has been observed in T parva-infected T-cell lines, with Fyn as the predominant Src kinase activity detected. 36 Permanent activation of lymphocytes by Theileria parasites induces production and secretion of cytokines, [37][38][39] and cell-cell contact is required for infected cell growth, 40 raising the possibility that surface receptor-activated Src kinases are involved in this process. We have demonstrated that proliferation of Theileria-transformed lymphocytes is phosphatidylinositiol-3-kinase (PI3-K) dependent.…”
Section: Introductionmentioning
confidence: 99%